Educators' perceptions and views of problem-based learning through simulation - Sidwell Matlala (AOSIS, 2021)
Background: The real-world problems and ever-changing challenges currently confronting the future of nursing education and healthcare require a problem-based learning approach using simulation strategy. This is exacerbated by the increasing burden of diseases such as tuberculosis, human immunodeficiency virus and acquired immune deficiency syndrome (HIV and AIDS) and more recently the coronavirus disease 2019 (COVID-19) pandemic, as well as advancing technology and changing regulations and policies. Problem-based learning is a student-centred learning strategy, where students are presented with situations drawn from practice, which can be used to bridge the theory-practice gap. Objectives: To explore the perceptions and views of healthcare educators on how problem-based learning can be facilitated through simulation. Method: A qualitative, exploratory, descriptive and contextual research design was used. Thirteen educators from the Faculty of Health Sciences of the University of Johannesburg, with 5 years' teaching experience, were purposively selected from the Dean's office, the Nursing Department, emergency medical care and the departments of podiatry, somatology and radiography. The participants were selected based on their extensive knowledge of problem-based learning and the use of simulation. Data were collected through in-depth, individual, semi-structured interviews. Thematic analysis provided six themes and 13 related sub-themes. The article focuses on the perceptions and views of educators regarding problem-based learning through simulation. Results: Problem-based learning through simulation allows students to work together in teams, which demonstrates a new modus operandi and renders a holistic approach to patient care. Conclusion: Problem-based learning through simulation should be utilised to encourage reflective knowledge exchange. Students from various departments can learn about new innovations, creativity and develop critical thinking when solving complex health-related problems.